Abnormal lipid metabolism induced apoptosis of spermatogenic cells by increasing testicular HSP60 protein expression. (6th September 2020) - Cheng, Lixian; Yi, Xue; Shi, Ying; Yu, Shuwei; Zhang, Liyuan; Wang, Jie; Su, Ping
Abstract: Long‐term consumption of high‐fat and high‐calorie foods not only causes obesity, but also may cause a decline in sperm quality in men. Rats with abnormal lipid metabolism (high‐fat rats) were established by high‐fat diet for 24 weeks. HE staining was used to observe the morphological changes of testis in rats, TUNEL and flow cytometer was used to detect the cell apoptosis in rat testis and in vitro. Immunohistochemistry and Western blotting were used to detect the expression of protein. After 24 weeks of high‐fat food feeding, the body weight, serum lipids and number of apoptotic spermatogenic cells in the high‐fat group rat were significantly higher than those in the control group. In vivo, the expression of HSP60 protein in testis of high‐fat rats was positive related to apoptosis of spermatogenic cells, cleaved caspase 3/caspase 3 protein expression and Bax/Bcl2 protein expression in testis of high‐fat rats. Proportion of apoptotic spermatogenic cells was increased by up‐regulation of HSP60 protein expression in vitro. Long‐term consumption of high‐fat diets can cause high expression of HSP60 and spermatogenic cells apoptosis in rats, while HSP60 over‐expression promotes spermatogenic cell apoptosis and MAPK signal pathway in vitro.